In vivo and in vitro analysis of cytogenotoxicity in populations living in abnormal conditions from Santos-Sao Vicente estuary - Alpire, Maria Esther Suarez; de Camargo, Elaine Aparecida [UNESP]; Cardoso, Caroline Margonato; Salvadori, Daisy Maria Favero [UNESP]; Pereira, Camilo Dias Seabra; Ribeiro, Daniel Araki (Springer Nature, 2020)
The aim of the study was to evaluate cyto- and genotoxic effects in populations living in subnormal clusters in Santos São Vicente estuary. For in vivo study, samples of buccal mucosa and peripheral blood cells were collected. Micronucleus assay and single-cell gel (comet) assay were performed. For in vitro study, Chinese ovary hamster (CHO) cells were exposed to contaminated water. The results showed that people living in the contaminated estuary have increased DNA damage in oral mucosa and peripheral blood cells, as detected in the micronucleus and comet assays respectively. In addition, estuarine water was able to promote cytotoxicity at the highest concentrations, as well as decrease the number of cells in the G1 phase. In summary, our results indicate that water from the Santos-São Vicente estuary is capable of inducing cytogenotoxicity in mammalian cells in vivo and in vitro.
Keywords: Comet assay; Cytotoxicity; Genotoxicity; Micronucleus assay; Santos-São Vicente estuary